2016
DOI: 10.1590/bjpt-rbf.2014.0184
|View full text |Cite
|
Sign up to set email alerts
|

Is handgrip strength normalized to body weight a useful tool to identify dynapenia and functional incapacity in post-menopausal women?

Abstract: ObjectiveTo investigate whether handgrip strength normalized to body weight could be a useful clinical tool to identify dynapenia and assess functional capacity in post-menopausal women. MethodA total of 136 postmenopausal women were recruited. Body composition (Dual Energy X-ray Absorptiometry [DEXA], Bio-electrical Impedence Analysis [BIA]), grip strength (dynamometer) and functional capacity (senior fitness tests) were evaluated. Dynapenia was established according to a handgrip strength index (handgrip str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The fact that strength measurement at a single time point has been shown to be predictive of mobility decline and 11 that the lower limbs are most affected 21 , 24 should make lower limb strength assessment a priority for researchers generating reference values for muscle health and clinicians in practice. As Dulac et al 46 have recently reported using handgrip strength, we report knee extensor strength normalised to body mass as an index that could provide a cost effective and simplistic measure of muscle health which could be used in a clinical setting and can represent a significant proportion of the variance in functional capacity. This may be useful to clinicians attempting to assess the functional capability of older adults in the community.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that strength measurement at a single time point has been shown to be predictive of mobility decline and 11 that the lower limbs are most affected 21 , 24 should make lower limb strength assessment a priority for researchers generating reference values for muscle health and clinicians in practice. As Dulac et al 46 have recently reported using handgrip strength, we report knee extensor strength normalised to body mass as an index that could provide a cost effective and simplistic measure of muscle health which could be used in a clinical setting and can represent a significant proportion of the variance in functional capacity. This may be useful to clinicians attempting to assess the functional capability of older adults in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were advised to squeeze as hard as possible the hand dynamometer for up to 4 s. Three measurements for each hand, alternatively, were performed and the maximal score for each was recorded. Upper limb muscle strength was expressed in absolute (kg) and relative (divided by body weight (BW; kg/kg)) values [41].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were advised to squeeze as hard as possible the hand dynamometer for up to 4 s. Three measurements for each hand, alternately, were performed and the maximal score of each was recorded. Upper limb muscle strength was expressed in absolute (ULMS; kg) and relative (ULMSr: divided by body weight (BW; kg/kg)) values [56].…”
Section: Maximum Voluntary Upper Limb Muscle Strength (Ulms)mentioning
confidence: 99%